The Role of Javanese Women in Domestic and Public Spheres: Challenges, Trade Motives, and Parenting Practices - Herlambang, Saifuddin; Suratman, Bayu; Kadir Naffati, Abdel (Islamic Early Childhood Education Study Program, Faculty of Tarbiyah and Education, UIN Sunan Kalijaga Yogyakarta, 2023)
Purpose – This study aims to explore the dual role of Javanese women who engage in trade at traditional markets and their role as mothers in parenting practices. Design/methods/approach – Employing qualitative research with an ethnographic approach, this study gathered primary data from interviews with Javanese women traders at the Karangawen traditional market, who have children aged 0–8 years. Data collection methods included semi-structured interviews, observations, and documentation. This was followed by a descriptive analysis of the findings. Findings – The study identifies three main motives for Javanese women trading in traditional markets: self-actualization, economic needs, and the pursuit of independence. Additionally, the study reveals various aspects of parenting practices among Javanese women. These include practices such as bancaan weton lair, weton lair fasting, and infant massage. Research implications/limitations – The research is constrained to a descriptive analysis, focusing on a limited data set regarding the roles of Javanese women as traders in the public sphere and as mothers in the domestic sphere. Practical implications – The study highlights the dual role of rural women, who are active in both the public sphere (through trading) and the domestic sphere (through parenting). This dual engagement reflects the multifaceted nature of their daily lives. Originality/value – The study underscores how culture, economy, and social environment shape parenting practices among Javanese women. Paper type Research paper